Roadmap of post-quantum cryptography standardization: Side-channel attacks and countermeasures - Shaller, Ari; Zamir, Linir; Nojoumian, Mehrdad (Information and computation, 2023)
Quantum computing utilizes properties of quantum physics to build a fast-computing machine that can perform quantum computations. This will eventually lead to faster and more efficient calculations especially when we deal with complex problems. However, there is a downside related to this hardware revolution since the security of widely used cryptographic schemes, e.g., RSA encryption scheme, relies on the hardness of certain mathematical problems that are known to be solved efficiently by quantum computers, i.e., making these protocols insecure. As such, while quantum computers most likely will not be available any time in the near future, it's necessary to create alternative solutions before quantum computers become a reality. This paper therefore provides a comprehensive review of attacks and countermeasures in Post-Quantum Cryptography (PQC) to portray a roadmap of PQC standardization, currently led by National Institute of Standards and Technology (NIST). More specifically, there has been a rise in the side-channel attacks against PQC schemes while the NIST standardization process is moving forward. We therefore focus on the side-channel attacks and countermeasures in major post-quantum cryptographic schemes, i.e., the final NIST candidates.